Efektivitas Studi Kelayakan Bisnis dalam Meningkatkan Penjualan Kentang di Koperasi Aspi Daranata Agro Priangan - Sulaeman, Ayra Zakirah; Sudrartono, Tiris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate the effectiveness of business feasibility studies in improving potato sales at the Aspi Daranata Agro Priangan Cooperative. Conducting feasibility assessments plays a pivotal role in the growth and expansion of cooperative businesses, but their impact on cooperative performance has not been widely studied. This research uses a qualitative approach with a case study method. Data were collected through interviews, observation and documentation. The results show that the business feasibility study conducted by the Aspi Daranata Agro Priangan Cooperative was effective in increasing potato sales. This is reflected in increased sales volume, expanded market reach and increased member satisfaction. Through the feasibility study, the cooperative can identify market potential, evaluate marketing strategies and allocate resources more optimally. The insight gained from this work highlights the requirement to empower the skills of cooperatives in conducting business feasibility studies on a regular basis to support business sustainability and member welfare.